Development of ground motion models for Northern South América - Nosam Gmms (2024)
The Northern South America (NoSAm) region, comprising Colombia, Ecuador, and Venezuela, is considered earthquake-prone due to its complex tectonic setting, driven by the interaction of three tectonic plates: Nazca, Caribbean, and South America. However, the recorded seismic history in the region is relatively recent, with the installation of the first digital strong motion networks in the late 1980s and early 1990s. The youth of these instrumental seismic networks poses a challenge for developing region-specific ground motion models that can adequately constrain extrapolation for design scenarios comprising high magnitudes earthquakes recorded at short distances. As a result, seismic hazard assessments in Colombia, Ecuador, and Venezuela rely on global and foreign Ground Motion Models (GMMs), highlighting the need for regional GMMs that consider the unique characteristics of the ground motion process in the region. To address these needs, this dissertation presents six ground motion models for estimating spectral accelerations and non-spectral intensity measures such as Arias intensity, Peak Ground Velocity, and Cumulative Absolute Velocity in NoSAm. These models allow the prediction of the intensity measures produced by earthquakes from the four tectonic environments in the region crustal, subduction interface, subduction intra-slab, and Bucaramanga nest. These GMMs will enhance and improve the understanding of seismic intensity attenuation throughout the region and future seismic hazard assessments.